Power Systems Analysis - Saadat, Hadi.; Saadat, Hadi. (New Delhi McGraw-Hill Primis Custom Publishing, 2010)
This text is intended for undergraduates studying power system analysis and design. It gives an introduction to fundamental concepts and modern topics with applications to real-world problems. This is the first text in this area to fully integrate MATLAB and SIMULINK throughout. It also provides students with an author-developed POWER TOOLBOX DISK organized to perform analyses and explore power system design issues with ease.
Keywords: System analysis; Electric power systems